Effect of pH on the Performance of Bi2O2CO3 Nanoplates for Methylene Blue Removal in Water by Adsorption and Photocatalysis - Trung Thanh Nguyen; Tri Thich Le; Thi Bao Tran Nguyen; Thuy Nguyen Thi; Thi Quynh Anh Nguyen; Le Ba Tran; Nhat Huy Nguyen (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
In this study, a facile low-temperature hydrothermal method was applied for the synthesis of bismuth subcarbonate nanoplates (Bi2O2CO3). The material was then characterized by FTIR, XRD, SEM, BET, and TGA. The applicability of Bi2O2CO3 was evaluated via the treatment of methyl blue (MB) in water by adsorption and photocatalytic degradation. The experiment results with different pH from 2 to 12 indicate that the pH of the solution affected the surface charge of the synthesized Bi2O2CO3, thus having strong effects on the adsorption and photocatalytic degradation abilities of Bi2O2CO3 for MB removal. In adsorption tests, pH 6–7 is the most suitable condition for the adsorption of Bi2O2CO3. In photocatalytic tests, Bi2O2CO3 had the highest and lowest efficiencies of 64.19% (pH 5) and 17.59% (pH 2), respectively, under UV irradiation for 300 min. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).